2020
DOI: 10.1186/s12920-020-0700-7
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis of HPV-induced warts and healthy skin in humans

Abstract: Background: The human papillomaviruses (HPV) are a group of viruses that, depending on the strain, can cause cancer or the formation of benign growths known as warts. Scarce information exists with regard to the genetic nature of non-genital cutaneous warts induced by the human papillomavirus (HPV). Methods: The main purpose of this study is to investigate the differences between the gene expression profiles of common warts and healthy skin in HPV-positive individuals by RNA sequencing on the Illumina HiSeq 25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 46 publications
0
14
0
1
Order By: Relevance
“… 18 HPV can enter the skin through tiny damages or epithelial cells on the mucosal surface and infect the basal keratinocytes of the genitals and oral mucosa through further damage and micro damage. 19 At present, more than 200 HPV subtypes have been found, of which about 40 are related to the occurrence of anal and genital CA. 20 These diseases that pose a serious threat to health often have no specific skin lesions in the early clinical stage, and most of the clinical manifestations are mainly itching in the affected area.…”
Section: Discussionmentioning
confidence: 99%
“… 18 HPV can enter the skin through tiny damages or epithelial cells on the mucosal surface and infect the basal keratinocytes of the genitals and oral mucosa through further damage and micro damage. 19 At present, more than 200 HPV subtypes have been found, of which about 40 are related to the occurrence of anal and genital CA. 20 These diseases that pose a serious threat to health often have no specific skin lesions in the early clinical stage, and most of the clinical manifestations are mainly itching in the affected area.…”
Section: Discussionmentioning
confidence: 99%
“…The biological pathway that was most significantly affected following incident HPV infection was neutrophil degranulation. Studies show that neutrophil degranulation is enhanced in HPV-induced dermal warts, and it is suggested that neutrophils are involved in cervical carcinogenesis by suppressing T-cell activity [ 13 , 14 , 15 ]. In contrast, the involvement of the immune system in the clearance of HPV infection did not turn out to be a biological pathway of major importance.…”
Section: Discussionmentioning
confidence: 99%
“…In 2000, 3 cases in which HPVXS2 (later discovered to be HPV78) was detected from squamous cell carcinoma and actinic keratosis of renal transplant recipients were reported (6). Since then, 7 additional cases of HPV78-related skin lesions have been reported (7)(8)(9). Among these 10 cases, 8 were associated with immunosuppressed or immunocompromised states due to renal transplantation (4/10), HIV infection (3/10), or splenectomy (1/10).…”
Section: Discussionmentioning
confidence: 99%